Water Quality and Sustainability: Addressing Challenges in the Context of SDGs - Praveena, Sarva Mangala (Mulawarman International Conference on Tropical Public Health, 2025)
This study examines the challenges associated with improving water quality and achieving Sustainable Development Goal 6: Clean Water and Sanitation. By analyzing existing literature and case studies, this research aims to identify the key factors that hinder progress in water quality management and to explore potential solutions. The findings will contribute to the development of more effective strategies for ensuring sustainable water resources. This study focuses on the emerging issue of microplastic pollution in water bodies. By reviewing the scientific literature and conducting a field study, this research aims to assess the extent of microplastic contamination in [Nama Wilayah] and to evaluate the potential impacts on aquatic ecosystems and human health. The findings will contribute to the development of effective strategies for mitigating microplastic pollution. This study examines the challenges of improving water quality in a rapidly urbanizing region in Southeast Asia. By analyzing water quality data and conducting interviews with local government officials and community members, this research identifies industrial discharge, agricultural runoff, and inadequate wastewater treatment as the primary causes of water pollution. The study highlights the need for integrated water resource management, strengthened regulatory frameworks, and increased public awareness to address these challenges and achieve Sustainable Development Goal 6.